Effect of Application of Liquid Organic Fertilizer of Pineapple Peel Waste on Growth and Production of Red Lettuce Plants (Lactuca sativa var. Crispa): Pengaruh Aplikasi Pupuk Organik Cair Limbah Kulit Nanas Terhadap Pertumbuhan Dan Produksi Tanaman Selada Merah (Lactuca sativa var. Crispa) - Kuswardina, Atik; Abror, M (Procedia of Engineering and Life Science, 2023)
This study aims to determine the effect of giving the optimal concentration of pineapple peel liquid organic fertilizer on the growth and production of red lettuce plants (Lactuca sativa var. Crispa)". This research was conducted in Modong Village, Tulangan Subdistrict, Sidoarjo Regency and continued at the Agrotechnology Laboratory of Muhammadiyah Sidoarjo University. The research was conducted from December 2022 to January 2023. This study uses a Randomized Group Design (RGD) with a single factor, namely the concentration of liquid organic fertilizer application of pineapple peel waste. The concentrations of liquid organic fertilizer of pineapple peel waste were 100 cc/l; 150 cc/l; 200 cc/l; 250 cc/l; 300 cc/l; 350 cc/l; 400 cc/l. The data obtained were processed using ANOVA, if there is a difference between treatments then it will be followed by 5% tukey test. The variables observed were plant height, number of leaves, wet weight, dry weight, root length, and harvest index. Based on the results of the study, it can be concluded that the application of liquid organic fertilizer pineapple peel waste significantly affects the observation variables of plant height, number of leaves, wet weight, dry weight and root length. While it is not significantly different on the observation variable of harvest index. The optimal application of liquid organic fertilizer pineapple peel waste is with a concentration of 250 cc/l (N4).